Vibrational spectroscopic, electronic influences, reactivity analysis and molecular docking studies of 2-Fluoro-4-iodo-5-methylpyridine. Issue 1 (2nd January 2023) - Selvakumari, S.; Venkataraju, C.; Muthu, S.; Sangeetha, P.; Rajesh, R.
Abstract: Geometrical optimization along with spectroscopic survey and electronic scrutiny of 2-Fluoro-4-iodo-5-methylpyridine were carried out by exercising Density-functional theory. The intramolecular hydrogen bonding interaction of the caption compound was investigated by means of the Natural Bond Orbital analysis. The Highest Occupied Molecular Orbital & Lowest Unoccupied Molecular Orbital energies, Mulliken charges, and Non-Linear Optic properties were procured in dissimilar liquids to analyze the solvent influence. The Theoretic Ultraviolet-visible spectrum of the investigation compound has been accomplished using Time-dependent density-functional theory in different solvents chosen. A Molecular Electrostatic Potential study has been achieved and conferred in terms of color distribution shows the reactive regions for protein interactions. Additionally, Electron localization function, Localized orbital locator and Reduced density gradient analysis of the caption compound were also studied. Furthermore, to reveal the biological importance of the caption compound, drug-likeness parameters have been computed and docking of the heading compound into the energetic site of the target proteins were performed to confirm that this compound has drug behavior.